ANALISIS PERBANDINGAN JUMLAH PENJUALAN PRODUK PERTAMINA DEX ANTARA SEBELUM DENGAN SESUDAH ADANYA MOBIL TANGKI PTO (POWER TAKE OFF) DI TERMINAL BBM REWULU YOGYAKARTA - Agus Mulyono; Dwi Wahyu Pril Ranto (Jurnal Bisnis, Manajemen, dan Akuntansi, 2018)
The sales of product “PertaminaDex” at Pertamina (Persero) Rewulu Fuel Terminal is currently at its early stage. The sales of PertaminaDex which were not as much as Premium and Diesel / Biodiesel has made it a challenge for Rewulu Fuel Terminal to find ways to enable PertaminaDex can be accepted in the market. Thereby, it would affect the increased sales The availability of PTO tankers is for product carrier of PertaminaDex . It is in order to provide more services as compared to other Petamina’s product. PTO tankers is a tank car that is equipped with Flow Meter and the dispenser, so that the gas station as the customer of Pertamina does not have to redeem a minimum of 8,000 liters to be able to get the product PertaminaDex, but it can make a purchase of at least 2,000 liters. Therefore, it is certainly very beneficial in reducing capital expenditure of the gas stations in buying PertaminaDex products at Pertamina (Persero) Rewulu Fuel Terminal. The objective of this study is to examine the comparison of product sales of PertaminaDex before and after the usage of tank car PTO owned by Pertamina (Persero) Rewulu Fuel Terminal. T- test was usedto analyze the different between the number of sales of the product 4 months before the use of PTO tank cars and 4 months after the use of the car. The results showed that there is no an increase of sales of the PertaminaDex after the use of the tank car at 10 percent level.